Production Optimization for Plan of Gas Field Development Using Marginal Cost Analysis - Soemardan, Suprapto; Purwanto, Widodo Wahyu; Arsegianto, Arsegianto (Makara Journal of Technology, 2013)
Gas production rate is one of the most important variables affecting the feasibility plan of gas field development. It take into account reservoir characteristics, gas reserves, number of wells, production facilities, government take and market conditions. In this research, a mathematical model of gas production optimization has been developed using marginal cost analysis in determining the optimum gas production rate for economic profit, by employing the case study of Matindok Field. The results show that the optimum gas production rate is mainly affected by gas price duration and time of gas delivery. When the price of gas increases, the optimum gas production rate will increase, and then it will become closer to the maximum production rate of the reservoir. Increasing the duration time of gas delivery will reduce the optimum gas production rate and increase maximum profit non-linearly.